Do directors have style? Board interlock and accounting properties. (7th September 2021) - Karim, Khondkar E.; Li, Jiayan; Lin, Karen Jingrong; Robin, Ashok
Abstract: We use the setting of board interlock (i.e., firms sharing directors) to examine whether director style influences accounting properties. We find that board interlock is associated with greater similarity in accounting properties such as accounting conservatism and reporting timeliness. Building on this result, we find a stronger similarity when the board member creating the board interlock holds a key position or when a greater number of board members create the board interlock. This evidence provides construct validity to the result that directors influence accounting policy as reflected in accounting properties (i.e., accounting conservatism and reporting timeliness). As further evidence, we find that the convergence in accounting properties is attributable to the director‐destination firm and that the director‐source firms' characteristics affect interlocking directors' influence over the director‐destination firms. Overall, our evidence affirms that directors have style in the sense that their distinct influence or imprint is evident in data on accounting properties. Moreover, our study indicates an actual process through which individual directors put their stamp on accounting policy.